Perancangan Produk Lilin Aromaterapi Brand Scentella Untuk Membantu Perempuan 20 Hingga 35 Tahun Mengatasi Insomnia - Charissa Belle Leticia; Paulina Tjandrawibawa (Jurnal Vicidi, 2022)
Insomnia is a condition where a person has difficulty sleeping and this is caused by several factors, one of the biggest is being stressed, and depression. Research shows that woman are more likely to experience the disorder than men, especially in the productive age, 20 to 35 years old. The methods that were used are both qualitative and quantitative, through surveys using questionnaires, user interviews and in depth research through journals and articles with credible sources. The results of the study show that aromatherapy candles can be a medium to help overcome Insomnia by helping to relax. Keywords: Scented Candles, Insomnia, Stress